2019
DOI: 10.1007/s10822-019-00195-y
|View full text |Cite
|
Sign up to set email alerts
|

ToGo-WF: prediction of RNA tertiary structures and RNA–RNA/protein interactions using the KNIME workflow

Abstract: Recent progress in molecular biology has revealed that many non-coding RNAs regulate gene expression or catalyze biochemical reactions in tumors, viruses and several other diseases. The tertiary structure of RNA molecules and RNA-RNA/ protein interaction sites are of increasing importance as potential targets for new medicines that treat a broad array of human diseases. Current RNA drugs are split into two groups: antisense RNA molecules and aptamers. In this report, we present a novel workflow to predict RNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…The photo‐crosslink is maintained throughout the simulations, and the average photo‐crosslinking distance from the 5 μs simulations is 6.0 ± 1.2 Å. The average photo‐crosslinking distance using the same definition reported in a previous MD simulation study over 1.5 ns of simulation time was 4.5 ± 0.7 Å 36 . It has been reported that the formation of the photo‐crosslink requires π stacking of U14 and the Cys10‐Cys27 disulfide bond 24 .…”
Section: Resultsmentioning
confidence: 74%
See 3 more Smart Citations
“…The photo‐crosslink is maintained throughout the simulations, and the average photo‐crosslinking distance from the 5 μs simulations is 6.0 ± 1.2 Å. The average photo‐crosslinking distance using the same definition reported in a previous MD simulation study over 1.5 ns of simulation time was 4.5 ± 0.7 Å 36 . It has been reported that the formation of the photo‐crosslink requires π stacking of U14 and the Cys10‐Cys27 disulfide bond 24 .…”
Section: Resultsmentioning
confidence: 74%
“…The average photo-crosslinking distance using the same definition reported in a previous MD simulation study over 1.5 ns of simulation time was 4.5 ± 0.7 Å. 36 It has been reported that the formation of the photo-crosslink requires π stacking of U14 and the Cys10-Cys27 disulfide bond. 24 Based on large changes in chemical shifts in NMR spectra of HBD induced by Macugen binding, it was suggested that Macugen interacts with two regions in HBD.…”
Section: Structures Of Hbd Macugen and Hbd-macugen Complexmentioning
confidence: 71%
See 2 more Smart Citations
“…3 D). Molecular docking technique analyzes the interaction forces between aptamers and target molecules through a variety of computational methods, and reveals this binding form between aptamer and target molecule [ 76 ]. Compared with the secondary structure prediction, molecular docking technology may be more intuitive and reliable.…”
Section: Post-selex Optimization Of Aptamersmentioning
confidence: 99%